2020
DOI: 10.47312/aifer.v3i01.251
|View full text |Cite
|
Sign up to set email alerts
|

EFISIENSI PEMBIAYAAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI JAWA TIMUR PERIODE 2014-2017. ANALISIS DENGAN METODE DEA (CRS,VRS, dan Skala)

Abstract: <p><em>This research aimed to find out the efficiency level of financing of Islamic Rural Bak in East Java. Input variables used were the rights of third party on profit sharing and PPAP cost, while output variable used was main operational income. Method used to measure efficiency level was Data Envelopment Analysis (DEA) with the assumption of Variable Return to Scale and the input and output orientations. The measurement of efficiency value with VRS assumption resulted three efficiency values, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of this study strengthen previous research conducted by Khairunnisa & Nisful (2018) and Khusnah et al (2020) regarding the analysis of the efficiency of BPRS in East Java. The cause of inefficiency is caused by the number of input variables that are greater than the target or the required amount, while the number of output variables is less than the target.…”
Section: Efficiency Analysis Using Deasupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study strengthen previous research conducted by Khairunnisa & Nisful (2018) and Khusnah et al (2020) regarding the analysis of the efficiency of BPRS in East Java. The cause of inefficiency is caused by the number of input variables that are greater than the target or the required amount, while the number of output variables is less than the target.…”
Section: Efficiency Analysis Using Deasupporting
confidence: 88%
“…The overall results of the BPRS can be said to have reached the level of efficiency. This research is also supported by Naufal & Firdaus (2017) but contradicts Fauzi (2018), Khairunnisa & Nisful (2018), and Khusnah et al (2020).…”
Section: Literature Reviewmentioning
confidence: 62%
See 1 more Smart Citation
“…The results of this study conclude that BPRS in East Java is classified as inefficient. Khairunnisa & Laila (2018) also explain the efficiency level of BPRS in East Java. The analysis found that the average BPRS in East Java showed inefficient efficiency during the study period.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Research on the efficiency of BPR and BPRS in East Java is still limited. Among these studies are Widiyaningtyas & Wura (2022), analyzing the financial performance comparison of BPR and BPRS East Java before and during the Covid-19 pandemic; Miranti et al (2022); Khusnas et al (2022) and Khairunnisa & Laila (2018) discuss the efficiency level of BPRS in East Java; and Almas (2018) examined the comparison of the efficiency of conventional BPR and sharia BPRS in East Java using a non-parametric approach.…”
Section: Introductionmentioning
confidence: 99%